Impulse oscillometry indices to detect an abnormal lung clearance index in childhood cystic fibrosis. Issue 12 (2nd September 2021) - Bokov, Plamen; Gerardin, Michele; Le Clainche, Laurence; Houdouin, Véronique; Delclaux, Christophe
Abstract: The objective of our cross‐sectional study was to assess the relationships between indices of multiple breath washout (MBW) and impulse oscillometry system (IOS) in cystic fibrosis in forty consecutive children (median age 8.1 years) in stable conditions and to evaluate whether cut‐off values of IOS indices may help to avoid MBW, which is time‐consuming. IOS measurements took a median duration of 3 min, while MBW measurements took a median duration of 49 min. Lung Clearance Index (LCI2.5% ) depicted significant linear correlations with z‐scores of R5Hz, R5‐20Hz, X5Hz, AX, and Fres ( r 2  = 0.27 to 0.51). Receiver‐operator characteristic curves were constructed and showed that the best compromise was obtained with the z‐score of Fres, with a cut‐off value of −1.37 that had a sensitivity of 0.966, a specificity of 0.636, and a negative predictive value of 0.875. This z‐score is useful for excluding increased LCI2.5% when below −1.37 using the reference set of Gochicoa et al. In conclusion, IOS measurement is easily and rapidly obtained in children and may be clinically useful for excluding increased LCI2.5%, thus allowing the time‐consuming MBW test to be avoided.